Foundations of Geometry : Selected proceedings of a conference - Scherk, Peter (Book collections on Project MUSE., 1976)
An unusual conference on the foundations of geometry was held in 1974 at the University of Toronto. It lasted from July 17 to August 18, a full four and a half weeks. A select group of leading geometers from Canada, the United States, West Germany, and other countries were invited to report at length on their recent advances.